Scopes of intervention and evolutionary paths for argentinian universities transfer offices*. Issue 5 (4th July 2019) - Becerra, Paulina; Codner, Darío Gabriel; Martin, Dominique Philippe
ABSTRACT: The majority of researches on knowledge and technology transfer from universities focused on the topic of processes which can improve the efficiency of the commercialization of R&D results. Furthermore, the different channels of transfer have been studied mainly independent of each other. This article develops a more strategic approach and proposes an integrated view of 16 channels of transfer organized around four core competences and considering their main form of governance. The empirical analysis is based on data gathered through a survey and an interview on a sample of 29 Argentinian National Universities publicly funded. The findings highlight four types of strategies – integral, network, entrepreneurial and undetermined – and two main types of potential evolutionary paths. The ability to differentiate the scopes of the intervention of universities transfer activities has implications for universities as well as for policymakers.